Optimization of Clean Water Distribution Networks at the Unima FMIPA Campus Using the Minimum Spanning Tree Method - Christari Lois Palit; Dyrel Samuel Lion Kusnadi (Griya Journal of Mathematics Education and Application, 2026)
The availability of clean water within higher education institutions is highly crucial to support the operations and convenience of the academic community. Issues regarding limited access to clean water were identified within the Faculty of Mathematics and Natural Sciences (FMIPA) at the State University of Manado, particularly in the Department of Mathematics Education. This study aims to model the clean water distribution network in FMIPA as a weighted graph and determine the optimal distribution path with minimum total pipe length using the Minimum Spanning Tree (MST) method via Prim’s Algorithm. This operations research-based quantitative study mapped six main nodes encompassing the water tank and departmental buildings. Distance data were obtained through digital map observations and Google Earth based on realistic piping pathways. The results indicate that optimization using Prim’s Algorithm produces an efficient single network configuration with the route: . This network successfully eliminates path redundancy, achieving a minimum total pipe length of 175 meters. Through this modeling, the Mathematics Education Department secures a reliable water supply delivered from the Science Education Building with a distance efficiency of only 25 meters. The implications of this research provide a practical recommendation for the university administration to efficiently optimize the allocation of plumbing material budgets.